Optimization of the OEE indicator through meta-models’ simulation in the buffer allocation problem - José Israel Hernández Vázquez; José Omar Hernández Vázquez; Salvador Hernández González; Daniel Arturo Olivares Vera (Journal of Industrial Engineering and Management, 2024)
Purpose: The buffer allocation problem (BAP) arises in the design of production systems; it involves analyzing and defining the optimal distribution of buffers within a production line. This paper presents a BAP formulation in a parallel series line from a cup sublimation process with unreliable operating conditions. The main objective of this study is to develop a new BAP solution proposal, considering the optimization of the OEE indicator used in Lean Manufacturing.